Organ Donation in the Emergency Department - Hickey, Michael (Université d'Ottawa / University of Ottawa, 2021)
Hundreds of Canadians die each year while awaiting a vital organ transplant. Consistent with several countries in the world, the demand for organs for transplantation outweighs the supply. In Canada, citizens must actively register to enlist themselves as organ donors after death occurs. The aim of this thesis was to examine and evaluate the acceptability of an emergency department-based organ donation registration strategy. Secondarily, we identified the proportion of emergency physicians, nurses and clerks who are personally registered as organ donors. We conducted three self-administered surveys as well as an a priori sub-study to evaluate the effect of a prenotification letter on postal surveys of physicians. We discovered that key stakeholders in emergency departments are engaged in organ donation and feel that the emergency department is an acceptable place to promote organ donation registration. In addition, we identified several barriers to such a potential intervention which largely revolve around time and resource limitations.
Keywords: Organ Donation; Emergency Department